2021
DOI: 10.1097/acm.0000000000003921
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of the Ottawa Surgical Competency Operating Room Evaluation (O-SCORE) Scale to Assess Medical Student Performance on Core EPAs in the Workplace: Findings From One Institution

Abstract: PurposeAssessment of the Core Entrustable Professional Activities for Entering Residency (Core EPAs) requires direct observation of learners in the workplace to support entrustment decisions. The purpose of this study was to examine the internal structure validity evidence of the Ottawa Surgical Competency Operating Room Evaluation (O-SCORE) scale when used to assess medical student performance in the Core EPAs across clinical clerkships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 44 publications
2
29
1
Order By: Relevance
“…The frequent assessor model seemed to increase variance attributed to the learner for the Chen scale in only 2 Core EPAs. Overall, these findings were similar to our previous study 4 involving only the Ottawa scale. Based on these findings in conjunction with prior evidence, we suggest that the root cause analysis for challenges associated with WBAs for the Core EPAs involves the lack of a true competency-based curriculum in UME; the choice of scale alone does not appear to impact performance.…”
Section: Methodssupporting
confidence: 92%
“…The frequent assessor model seemed to increase variance attributed to the learner for the Chen scale in only 2 Core EPAs. Overall, these findings were similar to our previous study 4 involving only the Ottawa scale. Based on these findings in conjunction with prior evidence, we suggest that the root cause analysis for challenges associated with WBAs for the Core EPAs involves the lack of a true competency-based curriculum in UME; the choice of scale alone does not appear to impact performance.…”
Section: Methodssupporting
confidence: 92%
“…A summary of the results following application of the frequent assessor model is found in Supplemental Digital Appendix 2, at http://links.lww.com/ ACADMED/B130. A comparison of the overall findings from this study with those of our previous study 34 is found in Table 3.…”
Section: Impact Of Frequent Assessorsmentioning
confidence: 52%
“…While that is of some concern, the moderate correlation observed between scores suggests that raters were able to select different levels of performance even when using both simultaneously. Third, in line with the experience from the Core EPA pilot and prior research, 28,29,34 we used modified versions of the Ottawa and Chen scales for our WBAs. It may be worth investigating whether the original scales perform better.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations